Salvia officinalis L. resilience under chromium stress: An integrated study of growth, physiology, biochemical changes and rosmarinic acid production - Ramakrishnan, Rashmi; Nagella, Praveen (Plant Science Today, 2024)
Medicinal plants are increasingly challenged by rising chromium (Cr) levels in agricultural soil and water bodies due to industrialization and human activities. This research examines the impact of various chromium concentrations on Salvia officinalis L., a medicinal herb, over 3 specific time periods: 30, 60 and 90 days. As the duration of Cr exposure increases, various growth parameters showed an upward trend at the lowest concentrations, with the most robust growth observed in the 20 ppm Cr treatment group after 90 days. However, higher chromium concentrations resulted in reduced plant growth compared to untreated plants. Chromium primarily accumulates in the roots, stems and leaves, with the highest accumulation observed at 100 ppm. However, chlorophyll content declined with prolonged Cr exposure, particularly at higher concentrations. Carbohydrate levels initially increased at lower Cr concentrations but decreased with greater exposure, while protein content consistently decreased with elevated Cr levels. Proline levels exhibited mixed responses, rising at lower concentrations and declining at higher ones. Malondialdehyde (MDA) content increased with higher Cr levels and extended exposure. The enzymatic antioxidant system showed an initial increase followed by a decline with prolonged exposure. Rosmarinic acid content increased with chromium (Cr) exposure upto 60 ppm but subsequently decreased beyond that threshold. In the first 30 days, plants treated with Cr demonstrated a 17 % increase in rosmarinic acid production compared to the control (48.9 mg/g DW). However, with continued Cr exposure, there was a decline in rosmarinic acid production ranging from 10 % to 20 % compared to the control level (67.02 mg/g DW) at 90 days post-treatment. These findings underscore the complex and contrasting responses of Salvia officinalis to Cr toxicity, highlighting the necessity for extended study into the core mechanisms governing these responses and the development of strategies to alleviate heavy metal stress in plants.